PARENTAL SOCIAL CONTROL IN THE USE OF SMARTPHONES AMONG SCHOOL- AGED CHILDREN AT SDN 01 SUNGAI KAKAP - Angraini, Dini Agra; Asriati, Nuraini; Fransisca, Stella (Universitas Tanjungpura, 2025)
This article aims to examine parental social control in the use of smartphones among school- aged children at SD Negeri 01 Sungai Kakap, Kubu Raya Regency. The research method used is descriptive qualitative. Data collection techniques employed in this study include observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. The research findings show that there are preventive, repressive, and curative actions taken to control smartphone usage. Preventive actions include giving advice and guiding children in their smartphone usage by setting time limits on screen time after school. Preventive advice from parents also addresses the negative impacts of excessive smartphone use and specifies what content is appropriate for children to access. Additionally, preventive warnings are issued by parents, such as reprimands when children exceed the designated screen time limits. Repressive actions have been implemented by parents, including sanctions for children who violate the time limits set by parents and monitoring children while they use smartphones. Curative actions, including mediation strategies, have also been carried out. Parents provide motivation and encourage children to engage in positive activities such as private tutoring, Quran reading lessons, and playing with peers in their environment.